Comparison between matrix and back-to-back converter in flywheel energy storage systems - Nguyen Hung Do; Sy Manh Ho; Quoc Tuan Le; Tung Hoang; Trong Minh Tran; Phuong Vu (Institute of Advanced Engineering and Science, 2022)
Flywheel energy storage systems (FESS) are considered as the grid integration of renewable energy sources due to their buit-in advantages such as fast response, long cycle life and flexibility in providing auxiliary services to the grid, such as frequency regulation, and voltage support. This paper introduces the structure and comparison results of matrix converter and back-to-back converter which integrated with axial flux permanent magnet motor (AFPM) in FESS. Two converters are functionally equivalent in terms of input power quality and energy regeneration capabilities but need to be compared in terms of performance testing with speed response. In this paper, the research results have been verified that matrix converters perform more effective than back-to-back converters.